Three burial coffin traditions in Upland Ilocos Sur - Canilao, Michael Armand (Cordillera Review : Journal of Philippine Culture and Society, 2012)
This paper presents the results of an archaeological survey conducted in 2012 in the towns of Quirino, Alilem, and Sugpon in upland Ilocos Sur. The survey established three burial coffin traditions practiced in the area, dating back to the 18th-19th century or even earlier. These three traditions were provisionally tagged by the archaeological team as the "Patiacan," "Apaya," and "Danac" traditions after the barangays where the burial coffins were discovered. Horizontal log coffins (the Patiacan and Apaya) were first documented in Benguet and Tiagan toward the end of the 19th century. the third burial coffin tradition, the Danac, however, has never been recorded in any burial site anywhere in the Philippines. The Danac coffins can be briefly described as vertical hollowed-out trunks with carved limestone lids. A preliminary analysis of the coffin traditions is offered in this paper, using whatever relevant data could be culled from archaeological, socio-historical, and ethnographic sources on the Bontoc, Kankana-ey, Ibaloy, and Bago ethnolinguistic groups of the Cordillera region in Northern Luzon.